A challenge‐response endoscopic sinus surgery specific checklist as an add‐on to standard surgical checklist: an evaluation of potential safety and quality improvement issues. Issue 7 (27th February 2018) - Sommer, Doron D.; Arbab‐Tafti, Sadaf; Farrokhyar, Forough; Tewfik, Marc; Vescan, Allan; Witterick, Ian J.; Rotenberg, Brian; Chandra, Rakesh; Weitzel, Erik K.; Wright, Erin; Ramakrishna, Jayant
Abstract : Background: The goal of this study was to develop and evaluate the impact of an aviation‐style challenge and response sinus surgery–specific checklist on potential safety and equipment issues during sinus surgery at a tertiary academic health center. The secondary goal was to assess the potential impact of use of the checklist on surgical times during, before, and after surgery. This initiative is designed to be utilized in conjunction with the "standard" World Health Organization (WHO) surgical checklist. Although endoscopic sinus surgery is generally considered a safe procedure, avoidable complications and potential safety concerns continue to occur. The WHO surgical checklist does not directly address certain surgery‐specific issues, which may be of particular relevance for endoscopic sinus surgery. Methods: This prospective observational pilot study monitored compliance with and compared the occurrence of safety and equipment issues before and after implementation of the checklist. Forty‐seven consecutive endoscopic surgeries were audited; the first 8 without the checklist and the following 39 with the checklist. The checklist was compiled by evaluating the patient journey, utilizing the available literature, expert consensus, and finally reevaluation with audit type cases. The final checklist was developed with all relevant stakeholders involved in a Delphi method. Results: Implementing this specific surgical checklist in 39 cases at our institution, allowed us to identify and rectify 35 separate instances of potentially unsafe, improper or inefficient preoperative setup. These incidents included issues with labeling of topical vasoconstrictor or injectable anesthetics (3, 7.7%) and availability, function and/or position of video monitors (2, 5.1%), endoscope (6, 15.4%), microdebrider (6, 15.4%), bipolar cautery (6, 15.4%), and suctions (12, 30.8%). Conclusion: The design and integration of this checklist for endoscopic sinus surgery, has helped improve efficiency and patient safety in the operating room setting.